Impact of the Preliminary Education Policy on North Central Region of Nigeria Primary School System - Oladimeji, Kazeem Adebayo (Journal of Techno-Social, 2022)
The study was carried out to investigate the impact of the preliminary education policy on the primary school system of the North Central region of Nigeria. The study aimed to advance the understanding of the perceived impact of preliminary education policy implementation on the primary school system. The research question focused on the perception of key stakeholders’ that could improve the full participation and facilitate the establishment of more quality primary schools in the region. A case study was employed with a purposeful sample of 16 semi-structured interviews which included combination of parents or guardians, preschool heads, primary school principals, and officials from the region. Themes were extracted through descriptive coding regarding the preschool education policy’s perceived strengths and opportunities for improvement from collected data transcripts. The emergent themes from the study included equality and social justice, education for all, and school readiness for next level. The results point to the need for collaboration and active participation of all key stakeholders towards effective preliminary education policy implementation